2011
DOI: 10.5539/jas.v3n3p25
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Mobility in a Soil with Long Term Manure Application

Abstract: The objective of this experiment was to determine the movement of different forms of phosphorus (P) in a clay loam soil with 33 years of manure application at the rate of 0, 30, 60 and 120 Mg ha -1 yr -1 . Soil samples were taken from 3 soil layers and subjected to leaching in packed soil column. Leachate was analyzed for total (P t ), inorganic (P i ) and organic P (P o ). Inorganic P accounted for about 70% of leachate P t . About 50% of P t in leachate was lost within the first 5 pore-volume (PV). While 2% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 43 publications
(36 reference statements)
0
11
0
1
Order By: Relevance
“…Accumulation of P, in the topsoil layers, has been reported in the literature (Ojekami et al 2011;Kang et al 2011;Rubaek et al 2013). In Brazil, annual applications of manure in areas with Dystric Xeropsamments of sandy texture in sub-humid region in the northeastern Brazil (Agreste) have caused accumulation of nutrients in the surface layer (Silva and Menezes 2007;Galvão et al 2008;Oliveira et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulation of P, in the topsoil layers, has been reported in the literature (Ojekami et al 2011;Kang et al 2011;Rubaek et al 2013). In Brazil, annual applications of manure in areas with Dystric Xeropsamments of sandy texture in sub-humid region in the northeastern Brazil (Agreste) have caused accumulation of nutrients in the surface layer (Silva and Menezes 2007;Galvão et al 2008;Oliveira et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that long-term fertilization with manure can promote changes in P adsorption influencing its dislocation into deeper layers of the soil profile (del Campillo et al 1999;Silva and Menezes 2007;Galvão et al 2008;Xavier et al 2009;Tarkalson and Leytem 2009;Ojekami et al 2011;Abdala et al 2012;Bhattacharyya et al 2015). In this regard, leaching of P may occur in soils saturated with P, even if there is no excessive input of P. Nelson et al (2005) found higher values of leached P than P in the inputs for soils saturated with P when precipitation was above the average, indicating that desorption of P contributed to 50% of leached P.…”
Section: Adsorption and Desorption Of Pmentioning
confidence: 99%
“…This is due to the interaction of P with organic and inorganic components of the soil resulting in a low value of this ion in the soil solution with reduced risk of loss by leaching. In spite of this, Ojekami et al (2011) showed, through a column leaching study, that the P could be lost through leaching especially at high rate of manure application. Along line 2, the retention of P by the soil may be evidenced by higher concentrations in the first meter of soil depth.…”
Section: Penmentioning
confidence: 79%
“…It is also important to know where the highest concentrations of soil nutrients are located, to analyze the impact on groundwater. Some studies have been done to identify spatial variability and dynamics of nitrates and phosphorus in soil and groundwater (Ojekami et al, 2011;Pena-Yewtukhiw et al, 2009). Usually, these studies require a great number of soil samples at different depths, which are operatively difficult and cost prohibitive to obtain.…”
Section: Introductionmentioning
confidence: 99%
“…El fósforo (P), por ejemplo, es considerado nutriente esencial en la fotosíntesis, la producción de Adenosín Trisfosfato (ATP), la reproducción vegetal, la formación de aminoácidos y proteínas, entre otros aspectos fisiológicos de las plantas, siendo fundamental en la dinámica interna de los agroecosistemas (Ojekami et al 2011). No obstante, aunque el P se encuentra en cantidades altas en la mayoría de los suelos, la fracción disponible para absorción por las plantas, es baja.…”
Section: Introductionunclassified